Tweet! Tweet!. - Priddy Books (New York, NY : Priddy Books, 2015)
Rhyming text introduces a variety of animals and the sounds they make.
Cover title.
"Priddy Books big ideas for little people"--Page 4 of cover.
"Touch and feel"--Cover.
Keywords: Textured books -- Specimens; Board books; Animals -- Fiction; Animal sounds -- Fiction; Textured books; Toy and movable books; Stories in rhyme; Board books; Animals -- Fiction; Animal sounds -- Fiction; Toy and movable books; Board books for children; Stories in rhyme